2018
DOI: 10.32505/atfaluna.v1i2.924
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Media Audio-Visual terhadap Kecerdasan Spiritual

Abstract: This research aims to determine the influence of audio-visual media on the intelligence of children worship in the TK Pembina Kecamatan Idi Rayeuk. This type of research is class action research (PTK), conducted in July 2018 to August 2018. This research consists of two cycles with four main activities that exist on each cycle, namely planning, observation action, Reflaksi. Data is analyized using qualitative data and quantitative data. The subject in this study was a child in TK Pembina. The data collection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The research results were conducted in class B1 children using three indicators; introducing daily prayers with teacher demands, imitating prayer movements in the correct order, and saying a prayer before and after doing something. Some research in also showed that spiritual intelligence in children is also influenced by audiovisual media (Authar, 2018), and study groups (Syarfina, 2020) so that the jarimatika method, which combines movement, sound, and cooperation, has a good effect in improving children's spiritual intelligence in terms of reading prayers.…”
Section: Graph Of Comparison Of Pre-test and Post-test Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results were conducted in class B1 children using three indicators; introducing daily prayers with teacher demands, imitating prayer movements in the correct order, and saying a prayer before and after doing something. Some research in also showed that spiritual intelligence in children is also influenced by audiovisual media (Authar, 2018), and study groups (Syarfina, 2020) so that the jarimatika method, which combines movement, sound, and cooperation, has a good effect in improving children's spiritual intelligence in terms of reading prayers.…”
Section: Graph Of Comparison Of Pre-test and Post-test Scoresmentioning
confidence: 99%
“…Children's spiritual intelligence from an early age significantly impacts their piety, intellectual and emotional in the future. The purpose of education from the religious aspect is to gain knowledge, appreciation and practice of religious values that can be a provision for the formation of a personality based on religious values reflected in their daily attitudes and behaviour (Authar, 2018). Facing things like this, necessary to increase the spiritual intelligence of children so that they know what is allowed or not to do, one of which is the learning pattern of memorizing daily prayers in early childhood using the jarimatika method.…”
Section: A Introductionmentioning
confidence: 99%
“…Media audio visual dapat memperlihatkan tayangan yang bisa menarik perhatiannya anak didik, sehingga pengalaman yang baru dapat dirasakan oleh anak melalui tampilan video menarik terkait dengan kecerdasan spiritualnya anak. (Authar, 2018) dalam proses pembelajaran media audio visual sangat berpengaruh sebagaimana Hamalik mengemukakan manfaat dalam belajar yaitu untuk meningkatkan minat belajar nya anak juga dapat meningkatkan motivasi belajarnya anak bahkan berdampak pada psikologisnya anak.…”
Section: Pembahasanunclassified